2010
DOI: 10.14742/ajet.1078
|View full text |Cite
|
Sign up to set email alerts
|

Analysing high school students' participation and interaction in an asynchronous online project-based learning environment

Abstract: This study aims to replicate and extend a previous study which was conducted on primary school students' asynchronous online project-based learning. In this study, 276 high school students' participation and interaction in a project-based learning environment was mediated by an asynchronous computer-mediated communication (CMC) tool. The students' high participation revealed their adaptability to this teacher-facilitated learning environment. However, in terms of interaction, these students' notes were found c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Based on the previous work [29] [30], for each phase of the analytical model, we will build a dictionary of keywords, which will be the subject of reference for the comparison of similarity with the words of the text of the messages posted.…”
Section: Interaction Analysis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous work [29] [30], for each phase of the analytical model, we will build a dictionary of keywords, which will be the subject of reference for the comparison of similarity with the words of the text of the messages posted.…”
Section: Interaction Analysis Modelmentioning
confidence: 99%
“…In our case studies we opted for the approach of One against all (1Vs 1). The One-on-One approach is a special case of the decomposition methods populated by Dietterich et al [29] Then the simplest classification rule can be written:…”
Section: F Multi-class Svm For Classification Of Semantic Relationsmentioning
confidence: 99%
“…Phase III-negotiation of meaning Stage 3-integration of ideas Phase IV-testing and modification Stage 4-resolution of dilemma Phase V-application of ideas, and students' self-reflective statements However, past empirical research suggests that high levels of knowledge construction rarely occur during actual asynchronous online discussions (Garrison 2007;Jamaludin and Quek 2006;Kanuka and Anderson 1998;Maor 2010;McLoughlin and Luca 2000;Meyer 2003;Osman and Herring 2007;Quek 2010;Vaughan and Garrison 2004).…”
Section: Stage 2-exploration Of Ideasmentioning
confidence: 99%
“…Chai and Khine (2006) also used Gunawardena et al's model and reported a distribution of 60, 20, 13, 4, and 3 % from phase I to V, respectively. Quek (2010) found that high school students' posts mainly consisted of phase I constructions (82.7 %). Researchers using Garrison et al's (2001) model have also concluded that the majority of students' online discussion posts involved the exploration of ideas, while a maximum of 10 % of these posts attained the highest level of resolution (Garrison 2007;Kanuka et al 2007;Meyer 2003;Vaughan and Garrison 2004).…”
Section: Stage 2-exploration Of Ideasmentioning
confidence: 99%
“…Interaction analysis model for examining the social construction of knowledge in computer conferencing according to Gunawardena et al [4] I Sharing/comparing of information II The discovery and exploration of dissonance or inconsistency among ideas, concepts, or statements III Negotiation of meaning/co-construction of knowledge IV Testing and modification of proposed synthesis or coconstruction V Agreement statement(s)/applications of newly constructed meaning These characteristics have led to studies that combined PjBL and information and communications technology (ICT) to promote the social construction of knowledge by overcoming dissonance. For example, Heo et al [9] implemented a PjBL program for undergraduate students, and Quek [10] implemented one for high-school students in online environments. As shown in Table 1, both cited Gunawardena et al [4] 's interaction analysis model for examining social construction of knowledge in computer conferencing as an indicator of the social construction of knowledge that overcame dissonance and measured the effects.…”
Section: Introductionmentioning
confidence: 99%